Effectiveness of Compassion-Focused Therapy (CFT) and Schema Therapy on Sexual Self-Concept and Marital Satisfaction in Infertile Women - Gholami Baker , Nikta; Pourahmadi, Elnaz; Jalali, Mohsen; Mirani, Arastoo (Psychology of Woman Journal, 2025)
Objective: This study aimed to compare the effectiveness of Compassion-Focused Therapy (CFT) and Schema Therapy (ST) on sexual self-concept and marital satisfaction in infertile women. Methods and Materials: A quasi-experimental design with pre-test, post-test, and one-month follow-up assessments and a control group was employed. Thirty infertile women from Tehran were selected through purposive sampling and randomly assigned to three groups: CFT (n=10), ST (n=10), and waitlist control (n=10). Participants in the CFT group received eight weekly group sessions based on standard CFT protocols, while those in the ST group received ten weekly group sessions of schema therapy. The control group did not receive any intervention during the study period. Data were collected using Snell’s Sexual Self-Concept Questionnaire and the ENRICH Marital Satisfaction Questionnaire. Data analysis was conducted using repeated measures ANOVA and multivariate analysis of covariance (MANCOVA). Findings: Results indicated that both CFT and ST significantly improved sexual self-concept and marital satisfaction compared to the control group (p < .001). Pairwise comparisons showed that in both treatment groups, improvements from pre-test to post-test and pre-test to follow-up were significant (p < .001), while differences between post-test and follow-up were not significant (p > .05). CFT demonstrated a significantly greater effect on marital satisfaction than ST (p < .05), though the two therapies did not differ significantly in their impact on sexual self-concept (p > .05). No significant changes were observed in the control group across any measures (p > .05). Conclusion: Both CFT and ST are effective interventions for improving sexual self-concept and marital satisfaction in infertile women. CFT may be particularly advantageous in enhancing marital satisfaction, likely due to its emphasis on emotional attunement and self-compassion practices.